(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In recent times, small and medium-sized enterprises (SMEs) have become a familiar form of business organization. They have a significant contribution on economic development creating significant number of jobs around the world. Elo (2005) mentions; SMEs are the largest source of employment which plays a considerable role at regional and international level enhancing innovativeness. According to the European commission the ratio of SMEs to the number of inhabitants are 58 SMEs per 1000 inhabitants (European commission 2011). Total workforce generated by SMEs was 33% on private sector in 2005 and it has increased to 59% (European Commission 2011). SMEs were struggling with economic and financial crises in 2008. Despite this fact, recent research has shown that most of the SMEs are in recovering phase. Nevertheless,SMEs have been contributing significant amount of growth in the economy. Therefore, the importance of SMEs cannot be neglected. Furthermore, SMEs are generating approximately 90 million jobs all around Europe with contribution on innovation and economic growth. (EU commission 2011).